Service Recovery Strategies to Maintain Guest Satisfaction at X Hotel in Jakarta - Ong, Karen (Universitas Bunda Mulia, 2024)
Various service issues has been researched as one of the factors that influenced Indonesia to lose its contribution to the economic growth during post Covid-19. One of the efforts the hospitality can do to solve the problem is to further innovate service quality of the hotel. However, service failures often occur as a result of not meeting the guests’ expectations, and so service recovery address these failures and restore the guests’ trust and satisfaction with effective methods, such as compensation, proactive communication, and personalized resolutions. This research examines the service recovery strategy of X Hotel, a luxury hotel in Jakarta known for its high standards of service. What will be examined are methods used by front line workers to address service failures, the management’s role in ensuring the effetiveness of the service recovery, and challenges encountered during the process of service recovery. The data will be collected through interviews with the management of the front line workers of X Hotel, which includes the manager of the Food and Beverages, the manager of the Front Office, and the manager of the Housekeeping. The findings highlight the importance of a structured framework as a guideline to implement service recovery with clear boundaries set to improve the speed and effectiveness of the compensation given. Aside from that, advanced systems such as HOTSOS system and guest feedback platform greatly enhance the hotel’s ability to track and analye service failures, prevent recurrence, and gain insights on guests’ expectations. Adopting this structured framework and investing in these advanced systems can enhance the effort of service recovery, making it important for X Hotel to maintain a competitive advantage in the luxury hospitality sector.